Letter: significant burden of nonalcoholic fatty liver disease with advanced fibrosis in the USA: a cross‐sectional analysis of 2011‐2014 National Health and Nutrition Examination Survey. Issue 5 (9th August 2018) - Liu, Y.; Wan, B.; Lin, S.
Abstract : Linked Content This article is linked to Wong et al and Wong papers. To view these articles visithttps://doi.org/10.1111/apt.14327 andhttps://doi.org/10.1111/apt.14909 .